Answer:
1. Correct
2. Correct
3. Incorrect
4. Correct
5. Correct
Step-by-step explanation:
Recall that: [tex]a^n=\frac{1}{a^{-n}}[/tex] and [tex]a^{-n}=\frac{1}{a^n}[/tex]
1. The first expression is [tex]x^{-2}y^2z^{-3}[/tex]. We rewrite as positive index to get:
[tex]x^{-2}y^2z^{-3}=\frac{y^2}{x^2z^3}[/tex]
2. The given expression is [tex]x^3y^{-2}z^{4}=\frac{x^3z^4}{y^2}[/tex]
3. The given expression is: [tex]x^{-3}y^{-2}z^2=\frac{z^2}{x^3y^2}[/tex]<-------This is the correct expression Not [tex]x^{-3}y^{-2}z^2=\frac{y^2}{x^3z^2}[/tex]
4. The expression is [tex]x^{-5}y^{-4}z^{-2}=\frac{1}{x^5y^4z^2}[/tex]
5. The expression is [tex]x^3y^{-4}z^{-6}=\frac{x^3}{y^4z^6}[/tex]